Effect of head rotation at the prone position on the geometric features of the healthy carotid bifurcation - Aristokleous, Nicolas; Seimenis, Ioannis; Papaharilaou, Yannis; Georgiou, Georgios C.; Brott, Brigitta C.; Anayiotos, Andreas (My University, 2010)
The influence of posture change on the geometry and hemodynamics of the carotid bifurcation has not been thoroughly studied [1,2,3]. Such changes may alter the hemodynamic variables that are generally associated with the development of atherosclerosis, such as low oscillating wall shear stress (WSS) and particle residence times. Glor et al. (2004) had reported changes in the right carotid bifurcation geometry with leftward rotation of the head. We have previously reported that geometric differences in the right and left carotid bifurcation occur with a rightward rotation of the head [3].
Keywords: Carotid bifurcation; Hemodynamics; Atherosclerosis